TT viral infection through blood transfusion: retrospective investigation on patients in a prospective study of post-transfusion hepatitis - Yang, Sien Sing (World J Gastroenterol, 2000)
AIM: To investigate the role of blood transfusion in TT viral infection (TTV). METHODS: We retrospectively studied serum samples from 192 trans fusion recipients who underwent cardiovascular surgery and blood transfusion between July 1991 and June 1992. All patients had a follow-up every other week for at least 6 months after transfusion. Eighty recipients received blood before screening donors for hepatitis C antibody (anti-HCV), and 112 recipients received screened blood. Recipients with alanine aminotransferase level > 2.5 times the upper normal limit were tested for serological markers for viral hepatitis A, B, C, G, Epstein Barr virus and cytomegalovirus. TTV infection was defined by t he positivity for serum TTV DNA using the polymerase chain reaction method. RESULTS: Eleven and three patients, who received anti-HCV uns creened and screened blood, respectively, had serum ALT levels > 90 IU/L. Five patients (HCV and TTV:1; HCV, HGV, and TTV:1; TTV:2; and CMV and TTV:1 ) were positive for TTV DNA, and four of them had sero-conversion of TTV DNA. CONCLUSION: TTV can be transmitted via blood transfusion. Two recipients infected by TTV alone may be associated with the hepatitis. However, whether TTV was the causal agent remains unsettled, and further studies are necessary to define the role of TTV infection in chronic hepatitis.